Benchmarking pavement practices in data-scarce regions – case of Saudi Arabia. Issue 3 (23rd February 2021) - Hamdar, Yara S.; Bakchan, Amal; Chehab, Ghassan R.; Al-Qadi, Imad; Little, Dallas
ABSTRACT: This study aims at employing the benchmarking strategy for assessing the state of the practice of the pavement industry in regions that have limited access to or lack the prerequisites for effective pavement practices. The research specifically seeks to propose a benchmark framework that identifies major categories and sub-categories necessary for effective evaluation of the state of practice of the pavement industry in data-scarce regions. The benchmark framework is developed and demonstrated for the case of Kingdom of Saudi Arabia (KSA), where pavement practices in KSA are benchmarked against those of select Gulf Cooperative Council (GCC) countries. For this purpose, data are collected based on a thorough review of literature and relevant industry documentation, as well as based on interviews with project stakeholders. Commonly adopted practices in North America, Europe, and Australia are used as a blueprint for identifying performance gaps and devising recommendations for improvement. Findings from this study would aid highway agencies and stakeholders in performing internal evaluation of their current state-of-practice and adapt the proposed framework to meet their local needs and constraints. Additionally, the paper provides a much-needed compilation of pavement-related data for the GCC countries—a data-scarce region.